Practical Linux Security Cookbook Secure Your Linux Environment from Modern-Day Attacks with Practical Recipes, 2nd Edition. - Kalsi, Tajinder (Packt Publishing Ltd, 2018)
Linux is often treated as a highly secure operating system. However, the reality is that Linux too has its own share of security flaws. These flaws allow attackers to get into your system and modify or even destroy your important data. This book will work as a practical guide for administrators and help them configure a more secure machine.